Polar Bear (Ursus Maritimus) Foraging Ecology in Western Hudson Bay - Sciullo, Luana (2018)
The ecological response of climate change is expected to be especially pronounced across the circumpolar Arctic. Predicted declines in sea ice extent and seasonal duration are expected to affect the foraging ecology of marine species, particularly polar bears (Ursus maritimus) that rely on stable sea ice patterns for various aspects of their life history. The goal of this thesis was to quantify body condition and characterize diet composition of polar bears in western Hudson Bay over a broad temporal scale (2004-2014), and identify potential environmental factors that may influence dietary shifts in one of the southernmost subpopulations of this species. Body condition was higher in adult and subadult females than males, consistent with energetic demands of gestation and lactation. Body condition also declined over time in adult and subadult males and females and was influenced by sea ice breakup and freeze-up dates. These trends suggest that the historical climate-driven declines in polar bear body condition documented in western Hudson Bay have continued. Variation in diet composition and dietary niche breadth across age, sex and reproductive groups suggest foraging behaviour is structured by energetic demands, intraspecific competition and sexual body-size dimorphism. Specifically, variation in diet and niche breadth across females was influenced by age (experience), energetic state and avoidance behaviours. Variation in diet composition and niche breadth between male and female bears, however, was more likely structured by body size, whereby capture of larger prey types and a broader range of prey species occurred with increasing body size. Body condition was positively related to niche breadth in adult males but negatively related to niche breadth in females with dependents, suggesting that less-selective foraging (scavenging) does not benefit body condition among reproductive females. Inter-annual fluctuations in diet composition reflected shifts in local prey availability during the study period, and sea ...